Identification and classification of epithelial cells in nephron segments by actin cytoskeleton patterns. (1st November 2019) - Kumaran, Girishkumar Kaitholil; Hanukoglu, Israel
Abstract : The basic functional unit in a kidney is the nephron, which is a long and morphologically segmented tubule. The nephron begins with a cluster of capillaries called glomerulus through which the blood is filtered into the Bowman's space. The filtrate flows through the nephron segments. During this flow, electrolytes and solutes are reabsorbed by channels and transport systems into the capillaries wrapped around the nephron. Many questions related to renal function focus on identifying the sites of expression of these systems. In this study, we mapped whole kidney sections by confocal microscopic imaging of fluorescent phalloidin, which binds to actin filaments. In tile scans (composed of hundreds of images) of these sections, the cortex and the medullary regions (outer and inner stripes of the outer medulla, and inner medulla) could be easily identified by their cytoskeletal patterns. At a higher resolution, we identified distinct features of the actin cytoskeleton in the apical, basal, and lateral borders of the cells. These features could be used to identify segments of a nephron (the proximal tubule, thin and thick segments of Henle's loop, and distal tubule), the collecting duct system, the papillary ducts in the papilla, and the urothelium that covers the pelvis. To verify our findings, we used additional markers, including aquaporin isoforms, cytokeratin 8‐18, and WGA lectin. This study highlights the power of high‐resolution confocal microscopy for identifying specific cell types using the simple probe of F‐actin‐binding phalloidin. Abstract : In this study, we mapped whole kidney sections by confocal microscopic imaging of fluorescent phalloidin that binds to actin filaments. At a high resolution, we identified actin cytoskeleton features of the apical, basal, and lateral borders of the epithelial cells to identify and distinguish between segments of a nephron (the proximal tubule, thin and thick segments of Henle's loop, and distal tubule) and the renal collecting duct system.